Solvent Transfer—Efficiency of Risk Management Measures. Issue 1 (19th November 2017) - Bluemlein, Katharina; Elend, Manfred; Meijster, Tim; Margary, Alison; Tibaldi, Rosalie; Hahn, Stefan; Hesse, Susanne
Abstract: A series of laboratory simulations were conducted in order to determine the airborne protection that might be afforded by different combinations of workplace exposure controls typically encountered when handling volatile solvents (e.g. solvent transfer). These conditions, referred to as risk management measures (RMMs) under the Registration, Evaluation and Authorisation of Chemicals Regulation (REACH), are typically described using standard phrases in safety data sheets [and specifically those of the European Phrase Catalogue (EUPhraC)]. Ethanol was used as a model compound and its emissions were monitored continuously with a portable IR spectrometer at 3000 cm −1 . The average emission reduction performance of the investigated RMMs (e.g. containment, extract ventilation, drum pump) exceeded 90%. They present suitable ways to reduce airborne solvent exposure in a workplace and confirmed the initial expectations derived at by the European Solvents Industry Group (ESIG) and the European Centre For Ecotoxicology and toxicology of Chemicals (ECETOC) Targeted Risk Assessment (TRA) model.